2018
DOI: 10.3390/rel9030070
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spirituality and Religiosity in Clinical Settings: A Scoping Review of Available Instruments

Abstract: Aims: Numerous measures exist that assess dimensions of spirituality and religiosity in health, theological and social settings. In this review, we aim to identify and evaluate measures assessing factors relating to spirituality and religiosity in clinical settings. Methods: A systematic literature search was conducted using PubMed, EMBASE and PsycINFO databases with search terms relating to spirituality, religiosity that also included well-being, needs, distress and beliefs used in self-reporting and clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 77 publications
1
37
1
3
Order By: Relevance
“…First, this review is limited to only 20 cross-sectional and questionnaire-based studies. In line with the conclusions of previous reviews of the literature regarding the role of religiosity/spirituality on health outcomes in different patient populations with pain-related and non-pain-related conditions (Austin et al 2018;Büssing et al 2007;Closs et al 2013;Jim et al 2015;Rippentrop et al 2005), the studies identified evidenced considerable methodological heterogeneity. The first source of studies heterogeneity regards the definition and operationalization of religiosity/spirituality constructs, with different studies using different measures covering different nonoverlapping dimensions of religiosity/spirituality.…”
Section: Strengths and Limitations Of The Current Systematic Reviewsupporting
confidence: 79%
See 1 more Smart Citation
“…First, this review is limited to only 20 cross-sectional and questionnaire-based studies. In line with the conclusions of previous reviews of the literature regarding the role of religiosity/spirituality on health outcomes in different patient populations with pain-related and non-pain-related conditions (Austin et al 2018;Büssing et al 2007;Closs et al 2013;Jim et al 2015;Rippentrop et al 2005), the studies identified evidenced considerable methodological heterogeneity. The first source of studies heterogeneity regards the definition and operationalization of religiosity/spirituality constructs, with different studies using different measures covering different nonoverlapping dimensions of religiosity/spirituality.…”
Section: Strengths and Limitations Of The Current Systematic Reviewsupporting
confidence: 79%
“…Terms are often used interchangeably or inconsistently and without operational definitions (Büssing et al 2007;Closs et al 2013;Rippentrop et al 2005). Moreover, measures used to assess both religiosity and spirituality often cover non-overlapping dimensions (Austin et al 2018;Jim et al 2015). For the purpose of this review, a person's religion or religious affiliation is operationalized as that person's self-report of belonging to a religious group (or not).…”
Section: Introductionmentioning
confidence: 99%
“…A scoping review of available instruments measuring spirituality and religiosity in clinical settings (Austin, Macdonald, & Macleod, 2018) studied some 25 instruments developed between 1989 and 2018. In almost all cases they were quantitatively based and only two instruments included elderly people.…”
Section: Spiritual Assessmentmentioning
confidence: 99%
“…One of the barriers of the absence of spirituality in health care is the subjectivity of the concept, and several measurement tools have been developed to measure its complex nature (Austin et al 2018). These revealed the positive influence of religion and spirituality on the physical (e.g.,: immune system functioning, longevity, dementia, heart diseases, hypertension, among others), mental (like anxiety, depression, and suicidal ideation), lifestyle (e.g., physical activity, smoking, sexuality, and others) and social aspects (such as marital relationships, social interactions, and social support) of a person's life (Koenig 2012;Lucchetti and Lucchetti 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These revealed the positive influence of religion and spirituality on the physical (e.g.,: immune system functioning, longevity, dementia, heart diseases, hypertension, among others), mental (like anxiety, depression, and suicidal ideation), lifestyle (e.g., physical activity, smoking, sexuality, and others) and social aspects (such as marital relationships, social interactions, and social support) of a person's life (Koenig 2012;Lucchetti and Lucchetti 2014). A recent review uncovered the existence of 75 tools from which 25 were found to be used in clinical environments (Austin et al 2018). A synthesis of Brazilian literature found only two instruments translated into European Portuguese (Lucchetti et al 2013).…”
Section: Introductionmentioning
confidence: 99%